2021
DOI: 10.1038/s41467-021-26835-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Escherichia coli cytochrome bd-II type oxidase with bound aurachin D

Abstract: Cytochrome bd quinol:O2 oxidoreductases are respiratory terminal oxidases so far only identified in prokaryotes, including several pathogenic bacteria. Escherichia coli contains two bd oxidases of which only the bd-I type is structurally characterized. Here, we report the structure of the Escherichia coli cytochrome bd-II type oxidase with the bound inhibitor aurachin D as obtained by electron cryo-microscopy at 3 Å resolution. The oxidase consists of subunits AppB, C and X that show an architecture similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 59 publications
2
58
0
Order By: Relevance
“…Despite its structural homology to CydA/AppC, the second large subunit CydB/AppB does not carry any metal-containing cofactors. Instead, for CydB of E. coli bd -I and AppB of E. coli bd -II, it has been found that a ubiquinone-8 or demethylmenaqinone-8 occupies a position equivalent to the heme binding sites in CydA/AppC ( Figure 2 C) [ 10 , 11 , 14 , 15 ], perfectly tracing the positions of the hemes in the opposing subunit. Hence, it has been postulated that this quinone has mainly stabilizing properties.…”
Section: Recent Advances In the Structural Biology Of Cytochrome ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Despite its structural homology to CydA/AppC, the second large subunit CydB/AppB does not carry any metal-containing cofactors. Instead, for CydB of E. coli bd -I and AppB of E. coli bd -II, it has been found that a ubiquinone-8 or demethylmenaqinone-8 occupies a position equivalent to the heme binding sites in CydA/AppC ( Figure 2 C) [ 10 , 11 , 14 , 15 ], perfectly tracing the positions of the hemes in the opposing subunit. Hence, it has been postulated that this quinone has mainly stabilizing properties.…”
Section: Recent Advances In the Structural Biology Of Cytochrome ...mentioning
confidence: 99%
“…Structural analyses of bacterial cytochrome bd oxidases by means of X-ray crystallography ( Geobacillus thermodenitrificans , pdb IDs 5DOQ & 5IR6, [ 9 ]) and cryo-electron microscopy (cryo-EM) ( Escherichia coli bd -I, pdb IDs 6RKO [ 11 ] and 6RX4 [ 10 ]; Mycobacterium smegmatis , 7D5I [ 12 ]; Mycobacterium tuberculosis , 7NKZ [ 13 ] and E. coli bd -II, 7OSE [ 14 ] and 7OY2 [ 15 ]) have shed light on the architecture of this class of oxidases.With the exception of the Geobacillus structures 5DOQ and 5IR6 that were obtained by X-ray crystallography, all structural data are based on cryo-EM. Resolutions range from 3.8 Å (5IR6, X-ray crystallography) to 2.5 Å (7NKZ, cryo-EM), providing near-atomic details (for a detailed discussion of optical resolutions in X-ray crystallography and cryo-EM, we suggest the work of Dubach and Guskov [ 85 ]).…”
Section: Recent Advances In the Structural Biology Of Cytochrome ...mentioning
confidence: 99%
See 3 more Smart Citations